(untitled) (Applied Biological Research, 2016)
The effect of feeding wild sunflower (Tithonia diversifolia) leaf meal (TDLM) on haemato-biochemical profiles of broilers was studied. Day old broiler chicks (180) were divided into six homogenous groups and fed rations with TDLM @ 0, 2, 4, 6, 8 and 10% as substitute of conventional ingredients for six weeks. The chicks were reared in battery brooder for first 14 days, and thereafter under deep litter system. Bloods were collected on 14th, 28th and 42nd day of age and haemato-biochemical parameters were estimated utilizing analytical kits. The study revealed that the average daily gain in body weight of broilers decreased with increased inclusion level of TDLM in ration and was significantly reduced above 4% inclusion level. The PCV and Hb values decreased (36.81±0.51- 31.25±0.70% and 12.47±0.35-9.40±0.71 g dL-1) and total RBC and WBC counts increased [4.20±0.12-6.43±0.09 (x10-6 mL-1) and4.13±0.13-6.40±0.58 (x10-3 mL-1)] increased inclusion level of TDLM in ration. All biochemical parameterswere variable throughout the feeding trial in all the groups. Total serum protein decreased with increased inclusion level of TDLM indicating alteration of normal protein metabolism. The GPT and GOT levels were higher at higher TDLM level but within the normal range. The serum Ca and P levels were variable but within the normal range. It was concluded that inclusion of TDLM upto 10% level as substitute of conventional ingredients has no significant effect on haemato-biochemical profiles of broilers although body weight gain is significantly reduced above 4% inclusion level of TDLM in the ration.